Comparison of "Will" Concept in Education and Jurisprudence and Possible Challenges in the Educational System of Iran and England - Mohsen Salehi Abari; mojtaba nikdoosti; Mohammad Jafari Fesharaki (Comparative Education Society of Iran ( CESIR), 2021)
The acceptance of man as a creature with a "will" is endorsed by all educational and legal systems, although the same intellectual and ideological foundations do not support this agreement. The purpose of this study was to investigate the concept of will and its consequences in the educational and legal systems of Iran and England. The research method is qualitatively comparative using document and content analysis methods for collecting and analyzing data. The research findings showed that there are similarities between the educational and legal systems of Iran and England in terms of accepting the idea that "human beings have a will". Another finding of the study revealed that in Iran, religious will prevails over individual and social will, and in England, individual will prevails over social and religious will. The research findings also indicated the dominance of "Islamic ideology" in Iran and "ideology of liberalism" in England over the concept of will in both educational and legal systems. In addition, the findings showed that when the concept of will enters the behavioral domains, it can make a difference in the performance of both educational and legal systems.